PERBANDINGAN PESAN POLITIK DALAM KONFERENSI PERS JOKOWI DAN PRABOWO PASCA PENDAFTARAN CAPRES 2019 - Kusno, Ali (SUAR BETANG, 2019)
Presidential and vice presidential candidates, Joko Widodo-Ma?ruf Amin and Prabowo-Sandi have been officialy registered as president and vice president candidates for Indonesia Presidential Election 2019. Both of president candidates gave a political speeches after registering at the KPU. Those speeches become a representation of their perception regarding presidential election 2019. That is why it is so important to reveal their political speech. This research used Fairclough?s critical discourse analysis. They both realize if the registration for presidential election just for the importance of Indonesian. Prabowo just give a different emphasis about KPU which have to guard the presidential election of 2019 that free from cheating. That point based on consideration if Prabowo as the president candidate who ever lose in presidential election of 2014 and has an argument if the defeat caused by cheating. Unfortunately, the commitment of pair of presidential and vice presidential candidate is still far from hope. The fact is everyday the community get a treated of bad political. Political that abuse each other and emmity. There is a parts who played the issues SARA to catch a sympathy the electors to get a dominance.